The Parish Pastoral Council for Responsible Voting (PPCRV) as an instrument of the Roman Catholic Church for clean elections the case of the Igbaras PPCRV - Diaz, Arnold G.
The Parish Pastoral Council for Responsible Voting (PPCRV) wa created by the Catholic Church in 1991 to help make the 1992 election and beyond clean and peaceful. This research is a study of one PPCRV unit in the Archdiocese of Jaro, the PPCRV in Igbaras in the 1982 and 1985 election., The researcher used three methods in this study---interview with key informants, survey questionnaire and library research. The study reveals that despite the great effort exerted by the PPCRV in both elections, its general contribution to the local elections in Igbaras was not really substantive. Electoral fraud, especially vote-buying, was still prevalent. yet, the PPCRV was able to raise the level of political intelligence and awareness of some voters and stopped the blatantness of the practice of vote-buying, a clear indication that the PPCRV's activities had a positive effect on the electorate, though a very small fraction of it, and the electoral process in Igbaras.